Model Pengembangan Kepemimpinan Islami Siswa di Sekolah: Analisis Interaksi Antara Kurikulum, Motivasi Belajar, dan Kinerja Guru - Sukarsih Sukarsih; Zulkarnain Zulkarnain; Gafar Alamsyah; Lukman Asha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aimed to develop a conceptual model representing interactions among Islamic education curriculum, student learning motivation, teacher performance, and student Islamic leadership development in five Madrasah Aliyah in Bengkulu, involving 100 teachers and 100 students. Using the Partial Least Squares Structural Equation Modeling (PLS SEM) method, this research succeeded in identifying empirical interactions among the aforesaid variables. The analysis results showed that the Islamic education curriculum had very large influences on student learning motivation and teacher performance with a T-statistic of 11.341 and 38.421 and a P-value of 0.000 for both. Apart from that, this research also found that student learning motivation had significant impacts on teacher performance and the development of students' Islamic Leadership, as evidenced by T-statistics of 3.585 and 106.232 and a P-value of 0.000. The indirect influential relationship between the curriculum through student learning motivation on teacher performance also showed statistical significance with a T-statistic of 3.046 and a P-value of 0.002, and the indirect influence of student learning motivation on Islamic leadership development through teacher performance with a T-statistic of 3.613 and a P-value of 0.000. These results confirmed that the model had been well-developed and well-confirmed. The results also emphasized the importance of a good curriculum and high learning motivation in improving teaching performance and developing student leadership based on Islamic values. Keywords: Islamic education curriculum, student learning motivation, teacher performance, and student Islamic leadership development